2019
DOI: 10.1007/s11356-019-04606-3
|View full text |Cite
|
Sign up to set email alerts
|

Difference of trace element exposed routes and their health risks between agriculture and pastoral areas in Bay County Xinjiang, China

Abstract: The concentration level related to toxicities of trace elements in drinking water, rice, wheat flour, and their associated negative impacts on human health have become an emergent issue in China. Because Xinjiang is the largest province in China with the majority of arable pasture landavailable for cultivation, it is important to analyse the concentrations of trace elements in relation to their toxicities in water, rice, and wheat flour and to investigate the health risk differences between agricultual and pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…One-way ANOVA results showed that the contents of seven trace elements were significantly different among three farmland soils except Ni (Table 1 and supporting information Table S5 ). This may be due to the multifactor functioning such as pollution source and the interaction between plants and soil 1 , 3 , 20 . For example, Zhu et al 45 , has shown that variance in plant accumulation capacity may cause variability of soil trace element content among different farmlands.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…One-way ANOVA results showed that the contents of seven trace elements were significantly different among three farmland soils except Ni (Table 1 and supporting information Table S5 ). This may be due to the multifactor functioning such as pollution source and the interaction between plants and soil 1 , 3 , 20 . For example, Zhu et al 45 , has shown that variance in plant accumulation capacity may cause variability of soil trace element content among different farmlands.…”
Section: Discussionmentioning
confidence: 99%
“…Large diesel- or gasoline-powered dispensers were used to harvest crops and spray pesticides. In these process, Hg and Zn from farm machinery tyres were likely added to soil 1 , 20 . Cr may have accumulated through the atmospheric settlement and irrigation 14 , 48 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations